Dystrophic Epidermolysis Bullosa in Goats - Medeiros, G. X.; Riet-Correa, F.; Barros, S. S.; Soares, M. P.; Dantas, A. F M; Galiza, G. J N; Simões, S. V D; Borges, Alexandre Secorun [UNESP] (Elsevier, 2013)
Clinical, histopathological and ultrastructural findings of caprine dystrophic epidermolysis bullosa (DEB) with autosomal recessive inheritance are reported. The goats presented with exungulation, erosions, crusts and scars on the skin and ulcers in the oral cavity. Microscopically, the skin showed subepidermal separation with clefts filled occasionally with clear eosinophilic fluid, cellular debris or neutrophils. Ultrastructurally, the site of blister formation was the sublamina densa in the epidermal basement membrane zone. In skin with blister formation and in clinically uninvolved skin, the basal lamina was preserved, but the anchoring fibrils were sparse and rudimentary. A twin brother of an affected kid was mated over 5 years with his mother; three out of the 10 kids born presented with epidermolysis bullosa, indicating that the disease has an autosomal recessive mode of inheritance. It is suggested that the disease is similar to human severe generalized recessive DEB. © 2012 Elsevier Ltd.
Keywords: Anchoring fibrils; Basal membrane; Epidermolysis bullosa; Goat; animal tissue; autopsy; autosomal recessive inheritance; basement membrane; blister; epidermolysis bullosa dystrophica; goat; hair follicle; hemidesmosome; histopathology; keratinocyte; malnutrition; mouth ulcer; neutrophil; nonhuman; priority journal; scar; Capra; Capra hircus